Transcriptome analysis reveals the pathogenesis of spontaneous tibial dyschondroplasia in broilers - Shi, Kai; Wu, Yongfu; Jiang, Xusheng; Liu, Xiangping; Du, Yuesong; Feng, Chungang; Li, Dongfeng (Frontiers in Genetics, 2024)
Tibial dyschondroplasia (TD) is a severe bone disease that affects fast-growing broiler chickens and causes economic loss. Despite previous studies, the regulatory mechanism of TD remains unclear and is thought to be primarily based on thiram induction, which may differ from that of naturally occurring diseases. To better understand TD, a digital X-ray machine was used in the present study to determine its incidence in four hundred yellow-feathered broiler chickens. The results showed that the incidence of TD was 22% after 6 weeks and gradually decreased after 8 and 10 weeks. The body weight of broilers with TD decreased significantly compared to that of NTD broilers. In addition, the length and density of the tibia were reduced after eight and ten weeks, and the density of the tibia was reduced after six weeks compared with the NTD chickens. This study also examined tibial quality parameters from TD (n = 12) and NTD broilers (n = 12) and found that bone mineral content, bone mineral density, bone ash content, calcium content, and phosphorus content were significantly reduced in TD broilers. Transcriptome analysis revealed 849 differentially expressed genes (DEGs) in the growth plate between TD (n = 6) and NTD groups (n = 6). These genes were enriched in ECM-receptor interaction, cytokine-cytokine receptor interaction, calcium signaling pathway, and TGF-β signaling. Genes encoding the alpha chain of type XII collagen, that is, COL1A1, COL5A1, and COL8A1) were identified as critical in the regulatory network of TD.Gene set enrichment analysis (GSEA) revealed that the pathways of cartilage development, circulatory system development, and nervous system development were changed in the growth plates of TD birds. In the blood transcriptome, 12 DEGs were found in TD (n = 4) and NTD chickens (n = 4), and GSEA revealed that the pathways from TD broilers' blood related to the phagosome, linoleic acid metabolism, monoatomic ion homeostasis, and calcium ion transport were downregulated. This study provides a comprehensive understanding of TD, including its effects on tibial quality, tibial changes, and the circulatory system, along with identifying important genes that may lead to the development of TD.